Implementing the Teaching Supervision by Principals in Improving the Performance of Teachers in Aceh Besar - Ashlan, Said (Jurnal Ilmiah Peuradeun, 2017)
Teaching supervision by principal in Aceh Besar State High Schools (especially in Excellent Senior High School 2 of Ali Hasjmy and Senior High School 1 Baitussalam) is one of factors to improve the quality of professional teacher performance. The purpose of this study was to identify the activities, techniques, implementations, supporting and inhibiting factors in teaching supervision by principals in improving teacher performance. The subjects of this research were principals, vice principals, and teachers. This study used qualitative approach and descriptive method. Meanwhile, the inhibiting factors of teaching supervision were the principals had other activities outside the school and did not have adequate time for the supervision, principal’s demonstration technique was still conventional, there was lack of fund, and there were teachers who were not creative and some of them were susceptible to illness (age factor).